Immigrant Children in a Pol(ICE) State - Silvia Rodriguez Vega (SAGE Publishing, 2022)
Guided by the following questions: (1) What are the experiences of immigrant children attending schools in communities experiencing police brutality and anti-immigrant sentiments? (2) How do middle school children of immigrants visually represent their experiences with legal violence? and (3) What are children's visions of freedom and community safety in this context?, this article highlights the understudied preadolescent children of immigrants through a 2-year study of a multidisciplinary theater class at a local elementary school in South Central Los Angeles. Data includes child interviews, class observations, artwork, and performance videos, from recently arrived Mexican and Central American children aged 10 to 13 years. Findings reveal how children come to understand policing, reinforcing concepts like "good cop/bad cop," conflating local police and ICE (Immigration and Customs Enforcement) agents, but also imagining alternatives for community safety outside of police systems. This work contributes to the fields of immigration, abolitionist education, and ethnic studies, among others, offering new ways of supporting immigrant children through the use of arts-based tools.